PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOGNITIF PADA PEMBELAJARAN PANCASILA DI SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low cognitive abilities of fifth-grade students at UPT SDN 010 Siabu. One solution to address this issue is to use the Problem Based Learning (PBL) model. The purpose of this study is to determine whether the use of the Problem Based Learning model has an effect on the learning process of fifth-grade students at UPT SDN 010 Siabu. The research method used is Quasi-Experimental, conducted with two classes: an experimental class and a control class. Each class had one learning session; the experimental class was taught using the Problem Based Learning model, while the control class used the Discovery Learning model. The subjects of this study were 20 students from class VA (control class) and 20 students from class VB (experimental class). Students' cognitive abilities were measured using pre-test and post-test data. The results showed that in the experimental class, the average pre-test score before applying the Problem Based Learning model was 68.0, and the average post-test score after applying the model increased to 90.0, showing a 22% improvement. In the control class, which used the Discovery Learning model, the average pre-test score was 57.5 and the post-test score was 73.5, showing a 16% improvement. Therefore, it can be concluded that the Problem Based Learning model has a positive effect on students’ cognitive abilities in Pancasila learning for fifth-grade students at UPT SDN 010 Siabu.